Wicked cool perl scripts: useful Perl scripts that solve difficult problems - Oualline, Steve (No Starch Press, Inc, 2006)
Most Perl programmers have been frustrated at one time or another because the system just wouldn't do what they wanted it to do. There was always that one simple and obvious utility that was missing that would make life so much easier -- a tool to get a stock quote, show off a photograph collection, or even display a collection of favorite comics. Wicked Cool Perl Scripts is about writing those utilities quickly and easily. With more than 100 handy utilities that solve difficult problems, Wicked Cool Perl Scripts is a great resource for the savvy Perl programmer.